تقييم مدى توافر الهيكل التنظيمي المناسب والقيم التنظيمية الداعمة, لنجاح تطبيق الإدارة الاستراتيجية (دراسة ميدانية على المنظمات الصناعية في محافظة اللاذقية). - ميا علي; ابراهيم حسين; سليطين سوما (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى تبيان الهيكل التنظيمي المناسب لنجاح تطبيق الإدارة الاستراتيجية وسمات القيم التنظيمية الداعمة لها, وإلى معرفة ماهية الفروق بين الهيكل التنظيمي والقيم التنظيمية في الشركات محل البحث وبينها, والتي تبين أنّها فروق جوهرية إيجابية, كما يهدف إلى تبيان كيفية وضع الخرائط التنظيمية بالمفهوم العلمي والتي يفترض تطبيقها لدعم أسلوب الادارة الاستراتيجية, وإلى معرفة الفروق بينها وبين كيفية وضع الخرائط التنظيمية في الشركات محل البحث والتي تبين أنها فروق جوهرية إيجابية. واعتمد البحث المنهج الوصفي التحليلي, واستخدم الاستبيان كأداة لجمع بيانات البحث, وتم تحليلها بواسطة البرنامج الإحصائي SPSS. وبنتيجة البحث تم التوصل إلى مجموعة من التوصيات أهمها: -ضرورة تحقيق مبدأ التوازن بين المركزية واللامركزية في الشركات محل البحث, -وجعل الإيمان بقيمة وأهمية الإدارة الاستراتيجية إحدى قيم المنظمة الجوهرية, -تحديث الوصف الوظيفي عندما تطرأ تغييرات تستدعي ذلك, -كتابة القيم التنظيمية للشركات في بيان لأنّ هذا يسهل خطوة من خطوات الإدارة الاستراتيجية وهي تحليل الثقافة التنظيمية. This research aims at figuring out the suitable organizational framework for successful application of strategic management as well as the features of the organizational values supporting it. It also handles the nature of differences of those features and the organizational framework and values within the companies under study. These differences have appeared to be essential and positive. The research finds out the methodology needed to form the organizational maps in its scientific concept. This methodology is supposed to be applied for supporting the strategic management. This research adopted the analytical descriptive approach and used the inference questionnaire methodology as means for collecting research information. The statistics program SPSS is used to analyze these pieces of information. The research issued the following recommendations: · The principle of centralization and decentralization should be adopted within the companies under study. · Appreciating the value and the importance of strategic management and adopting it as the company’s essential value. · Updating the functional description when new changes are involved. · Writing the organizational values as a separate statement because it will make the analysis of organizational culture easier.